CD73 Dysregulates Monocyte Anti-Tumor Activity in Multiple Myeloma - Zhou L; Liu X; Guan T; Xu H; Wei F (Cancer Management and Research, 2023)
Lin Zhou,1,* XiaoLan Liu,2,* Tao Guan,2 HaiLing Xu,1 Fang Wei1 1Department of Hematology, The First Hospital of Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 2Shanxi Key Laboratory of Precise and Diagnosis and Therapy of Lymphoma, Shanxi Province Cancer Hospital, Taiyuan, Shanxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fang Wei, Department of Hematology, The First Hospital of Shanxi Medical University, 85 Jiefang South Road, Yingze District, Taiyuan, Shanxi, People’s Republic of China, Tel +86 15034078883, Email 2649929367@qq.comPurpose: Multiple myeloma (MM) is characterized by immune cell dysfunction in the tumor microenvironment (TME). We aimed at evaluating the effect of CD73, an overexpressed factor in some tumors, on anti-tumor immune function in the TME of MM.Patients and Methods: We analyzed the expression of CD73 in T-, B-, and natural killer (NK)-lymphocytes and monocytes in bone marrow (BM), peripheral blood (PB) from MM patients and healthy controls, and residual CD138+ cells using flow cytometry. The anti-tumor activity of these monocytes was confirmed by co-culture with RPMI-8226 cells treated with a CD73 inhibitor. We determined the interleukin (IL)-2, IL-4, IL-6, IL-10, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ levels using a cytometric bead array. Monocyte phagocytosis in cell culture sediment was then observed and measured.Results: CD73 was highly expressed in T-, B-, and NK-lymphocytes and monocytes from the BM and PB isolated from patients with MM. Compared with healthy controls, MM samples exhibited significantly higher CD73 expression and TNF-α, IFN-γ, IL-10 levels in monocytes. Inhibiting CD73 in BM immune cells from MM samples significantly increased the secretion of IL-2, TNF-α, and IFN-γ, as well as the killing ability of immune cells. However, monocyte phagocytosis was seldom observed. Inhibiting CD73 in MM monocytes significantly increased the secretion of IL-2, TNF-α, and IFN-γ in monocytes and improved monocyte killing and phagocytosis.Conclusion: Monocytes from MM exhibited weakened anti-tumor effects, and CD73 was involved in forming an immunosuppressive microenvironment. Inhibiting CD73 partly restored the anti-tumor activity of monocytes, a potential strategy for the treatment of MM.Keywords: multiple myeloma, CD73, anti-tumor activity, monocytes, immune cells, phagocytosis